Exploring new protein-based scaffolds for bioengineering applications - Dias, Ana Margarida Gonçalves Carvalho (2016)
The potential of WW domains as proteins scaffolds for the development of purification affinity reagents has been explored. Minimal versions of native human Pin1 (hPin1_WW) and human YAP65 (hYAP65_WW) WW domains were produced through chemical synthesis using solid-phase peptide synthesis. After purification, characterization by mass spectrometry and circular dichroism demonstrated, respectively, the correct molecular mass, and the correct folding of WW domains with thermal stability comparable to the extended version expressed biologically. These peptides were further immobilized in chromatographic supports. Adsorbents bearing hPin1_WW captured phosphorylated peptides and proteins, whereas those modified with hYAP65_WW captured Proline-rich peptides. In both cases the binding and elution of the target peptides was achieved under mild conditions. Encouraged by these results, a näive library based on the sequence of WW prototype was designed and generated. The library was further evolved in vitro through phage and ribosome display methodologies against Human Serum Albumin (HSA) and Immunoglobulin G (IgG). The phage display library leads to the identification of CW3S (a WW domain derived from Clone 3) as a potential HSA binder. This ligand was produced biologically in co-expression with GFP, and was also chemically synthesized. The affinity between CW3S and HSA was determined as Ka of 8.37x106 M-1 (KD=119nM) by ELISA. The chemically synthesized peptide was characterized by circular dichroism showing the folding and thermal stability similar to other native WW domains. This peptide was also immobilized in agarose and captured HSA (0.291μg protein/mg support at 4°C). This work strongly demonstrated the robustness of the WW domains to withstand modifications and mutations, therefore possessing a clear potential for application as a protein scaffold.